Modified Ginzburg-Landau equation and Benjamin-Feir instability - Kengne, E. (Нелінійні коливання, 2003)
In this paper the modulated wave train in nonlinear monoinductance LC circuit is studied. Using the method of multiple scales in general form, we establish that the evolution of nonlinear excitations is governed by what we called the Modified Ginzburg – Landau Equation (MGLE). Benjamin – Feir instability for the MGLE is analyzed